Peningkatan Potensi Desa Wisata Denai Lama Melalui Edukasi dan SDGs: Increasing the Potential of Old Trail Tourism Villages Through Education and SDGs - Sujai Tanjung, Ahmad; Yulia, Yulia; Fitri, Fitri; Tia, Tia; Annisa, Annisa; Nurul, Nurul; Nadila, Nadila (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to find out how to increase the potential of the Old Denai tourist village through education and SDGs. This type of research uses qualitative methods with a descriptive approach. The informants for this research are the head of Denai Lama Village, Chair of the Sanggar Circle Foundation, MSME Culinary Traders and Tourists. Data collection techniques in this research are interview and observation techniques. The data analysis technique in this research uses data reduction, data display, and conclusion verification. Increasing the potential of the Denai Lama tourist village through education and implementing sustainable development goals (SDGs) aims to optimize local resources and improve the welfare of local communities. This research examines how education based on SDGs principles can support sustainable tourism development in the village. By focusing on strengthening human resource capacity, environmental conservation, and local economic empowerment, this strategy is expected to create tourism villages that are environmentally friendly, inclusive, and sustainable. This research also highlights the importance of collaboration between government, society and the private sector in creating a developing tourist village by integrating SDGs principles, in order to increase tourist attraction, improve quality of life, and preserve culture and nature in Denai Lama.